2002
DOI: 10.1210/jcem.87.6.8567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pioglitazone on Abdominal Fat Distribution and Insulin Sensitivity in Type 2 Diabetic Patients

Abstract: We examined the effect of pioglitazone on abdominal fat distribution to elucidate the mechanisms via which pioglitazone improves insulin resistance in patients with type 2 diabetes mellitus. Thirteen type 2 diabetic patients (nine men and four women; age, 52 +/- 3 yr; body mass index, 29.0 +/- 1.1 kg/m(2)), who were being treated with a stable dose of sulfonylurea (n = 7) or with diet alone (n = 6), received pioglitazone (45 mg/d) for 16 wk. Before and after pioglitazone treatment, subjects underwent a 75-g or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
187
2
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 554 publications
(211 citation statements)
references
References 42 publications
19
187
2
3
Order By: Relevance
“…Peroxisome proliferator-activated receptor gamma (PPARĪ³) agonist treatment is associated with decreased peripheral adipocyte lipolysis, decreased free fatty acid levels and fat redistribution toward peripheral fat (93). In PCOS, PPARĪ³ agonist treatment increased insulin sensitivity, improved ovulatory function and decreased inflammatory markers without significant effects on testosterone levels (94).…”
Section: Bone Mineral Density and Fracturesmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor gamma (PPARĪ³) agonist treatment is associated with decreased peripheral adipocyte lipolysis, decreased free fatty acid levels and fat redistribution toward peripheral fat (93). In PCOS, PPARĪ³ agonist treatment increased insulin sensitivity, improved ovulatory function and decreased inflammatory markers without significant effects on testosterone levels (94).…”
Section: Bone Mineral Density and Fracturesmentioning
confidence: 99%
“…Pioglitazone is a peroxisome proliferator-activated receptor Ī³ agonist that, in addition to its primary effect on glycemic control, exerts potential beneficial effects on inflammation, fat distribution, lipid and protein metabolism, and vascular endothelial function. [12][13][14][15] The IRIS trial (Insulin Resistance Intervention After Stroke) found that among patients without diabetes mellitus who had insulin resistance along with a recent history of ischemic stroke or TIA, the risk of combined stroke or myocardial infarction was lower among patients who received pioglitazone than among those who received placebo, but differences in recurrent stroke alone did not reach statistical significance. 16 The objective of this study was to use the totality of the published literature to qualitatively and quantitatively evaluate the risk of recurrent stroke in stroke patients with abnormal glucose metabolism receiving pioglitazone therapy, by conducting a systematic review and meta-analysis of randomized controlled trials.…”
mentioning
confidence: 99%
“…In a defined serum-free medium, PPARā„ agonists markedly enhance the differentiation of preadipocytes isolated from SF but not of preadipocytes from VF of same individuals (54). In vivo, subcutaneous but not visceral fat expands in response to PPARā„ agonists (55,56). The mechanisms by which SF and VF have different sensitivities to PPARā„ agonists are still unknown.…”
Section: Discussionmentioning
confidence: 99%